2022
DOI: 10.1002/adom.202202304
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Bright White Light Emission with Ultra‐High Color Rendering Index Induced by Trigonal Bipyramid Unit

Abstract: Efficient broadband emitting organic–inorganic metal hybrids (OIMHs) have attracted great attention recently as promising single‐component white light emitters. Here a new zero‐dimensional (0D) OIMH (C13H14N)2InCl5 (C13H14N+ = N‐methyldiphenylammonium) is reported, which features unique five‐coordinated [InCl5]2− trigonal bipyramid motif. For the first time, it is demonstrated that the trigonal bipyramid units in 0D OIMH can act as luminescence centers, showing blue emission under UV light. Remarkably, incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…To our knowledge, among the reported fivecoordinated In-based OIMHs, only (C 13 H 14 N) 2 InCl 5 shows blue emission with a photoluminescence quantum yield (PLQY) of 5.44%, while (C 20 H 20 P) 2 InCl 5 and (C 6 H 18 N 2 )InCl 5 ÁH 2 O hardly exhibit emission. [12][13][14] Hence, the development of 0D In-based OIMHs with [InX 5 ] 2À square pyramids and higher energy emission is beneficial to enrich the structure and luminescence of indium hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, among the reported fivecoordinated In-based OIMHs, only (C 13 H 14 N) 2 InCl 5 shows blue emission with a photoluminescence quantum yield (PLQY) of 5.44%, while (C 20 H 20 P) 2 InCl 5 and (C 6 H 18 N 2 )InCl 5 ÁH 2 O hardly exhibit emission. [12][13][14] Hence, the development of 0D In-based OIMHs with [InX 5 ] 2À square pyramids and higher energy emission is beneficial to enrich the structure and luminescence of indium hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…electronic configurations has been proven to be an effective strategy for improving photophysical properties. [18][19][20][21] Sb 3+ is an effective dopant used as a non-emitting system to activate photoluminescence (PL) emission due to the unique dynamic lone pair of electrons. 22,23 It is possible to realize efficient luminescence by constructing a host-guest doping system, in which the inert host is doped with a luminescent species.…”
Section: Introductionmentioning
confidence: 99%
“…electronic configurations has been proven to be an effective strategy for improving photophysical properties. 18–21 Sb 3+ is an effective dopant used as a non-emitting system to activate photoluminescence (PL) emission due to the unique dynamic lone pair of electrons. 22,23…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, researchers have found that zero-dimensional ionic indium-based IOMHs are stable and low-toxicity materials with excellent luminescence properties. Notably, while possessing organic cations, the anionic indium halide moieties in these ionic IOMHs are mostly pure inorganic such as octahedral (InX 6 ) 3– , conical (InX 5 ) 2– , tetrahedral (InX 4 ) − , , and dimeric (In 2 X 10 ) 4– (X = Cl, Br, I). , As is known, the coordination of organic ligands such as conjugated 2,2′-bipyridal and 1,10-phenanthroline (Phen) into inorganic halometalate units can lead to colorful PL arising from various mechanisms such as halogen-to-ligand charge transfer, ligand-to-metal charge transfer, and inorganic-to-organic charge transfer (IOCT). Thus, it is anticipated that different combinations of organic ligands and cations can make the PL properties of indium-based IOMHs highly adjustable due to the variety of PL mechanisms and supramolecular interactions inside.…”
Section: Introductionmentioning
confidence: 99%